The Influence of Family Communication on Generation Z's Marital Readiness: A Phenomenological Study in Martapura - Rini Fauziah (Divisi Penelitian dan Pengabdian Masyarakat Yayasan Cerdas Pedia Indonesia, 2026)
Marriage decisions among Generation Z are influenced by numerous factors, particularly the role of the family in providing guidance. This study aims to analyze the implementation of parental functions and the effectiveness of family-based marriage education on the marital decisions of Gen Z students. The research employed a qualitative method with a phenomenological approach, conducting in-depth interviews with 20 students at the Darussalam Martapura Islamic Institute. The findings reveal that a majority (65%) of parents have not optimally fulfilled their marriage education function, which correlates with a high level of marital unpreparedness among students (80%). It was found that 65% of respondents rarely communicate openly about marriage with their families, as the topic is often considered taboo. Conversely, the 35% of respondents who felt they received comprehensive parental guidance expressed better readiness. In conclusion, the lack of direct education and open dialogue within the family is a key factor contributing to the hesitation and postponement of marriage decisions among Generation Z.